Teacher Readiness in the Habitual Phase of the School Literacy Movement in Elementary School - Balqis, Assyuqia; Kurniaman, Otang; Permana, Dede (Raja Zulkarnain Education Foundation, 2025)
This research is motivated by the importance of the role of teachers in building a literacy culture from an early age through the GLS Habituation Stage in Elementary Schools. The purpose of this study is to analyze the level of readiness of elementary school teachers in the aspect of GLS habituation skills and principles, as well as to analyze teachers' readiness in the implementation of GLS habituation activities. Types of descriptive quantitative research with surveys. The population of 328 teachers in 11 elementary schools that are members of the Lancang Kuning Cluster, Pekanbaru City, with a sample of 180 teachers was selected by proportional random sampling with an error rate of 5%. This instrument is a 44-point Likert questionnaire consisting of nine GLS Habituation Stage indicators and has been tested for high validity and reliability (α Cronbach = 0.980). The data were analyzed descriptively based on frequency, mean, and standard deviation. The results of the study showed that the average total teacher readiness was 3.99 (high category). The highest indicators included literacy skills (4.41), the principle of focus and habituation (4.37), and the principle of reading activity (4.35), all in the very high category. Other indicators are literacy-rich environment (3.84), 15-minute reading program (3.89), facility arrangement (3.83), text-rich environment (3.96), and book selection (4.12) which range from the high category. The lowest public engagement (3.18; medium category) indicates the need to strengthen school, parent and community partnerships. It was concluded that elementary school teachers in the Lancang Kuning Cluster generally have high readiness at the GLS Habituation Stage, by further increasing community involvement.